Potential of fish scales as a filling material in surface coating of cellulosic paper - URAL, ELİF; ARMAN KANDIRMAZ, EMİNE (My University, 2018)
Background: Paper is one of the important inputs for the printing industry, and the most important leading parameter in the printing process is its brightness. Brightness can be brought to paper using coatings and sizing. Desired surface properties and, most importantly, surface roughness can be achieved by changing the contents of the coating and sizing of the materials it contains. The use of biomaterials is becoming more important in the paper industry, as they represent substances with a lower carbon footprint. Fish scales are already used as a filling material, cosmetic material and fish food, as well as for determining the age of fish. Methods: Fish scales were brought to different sizes by a milling process. Paper formulations including different amounts of fish scales were prepared with fish scales, and coatings on raw paper were subjected to test printings in IGT-C1, with formulations and physical characteristics of coatings such as brightness, lightfastness, strength, adhesion etc. being determined. Results: Regarding the value of yellowness, mixtures of 2.5%-10% can be used. The maximum value of brightness was obtained from a mixture of 10%. Aging visibly changed the colors. Conclusions: The coatings obtained were brighter than the initial coating compositions. The top quality formulation was the coating with 5% medium-sized fish scale particles.